Endophytic Fungi from Piper retrofractum VAHL: Isolation, Phytochemical Analysis, Antibacterial and Antioxidant Activities - Dwi Koko Pratoko (Journal of Global Pharma Technology, 2020)
Objective: Piper retrofractum Vahl. is an Indonesian plant that has several activities such as antibacterial, antifungal, antioxidant, etc. Endophytic fungi are fungal microbe which can produce secondary metabolites that associated with medical plants can be exploited for curing many diseases. This is the first study of endophytic fungi from P. retrofractum which can be an alternative source of natural product besides its host, P. retrofractum. Seven endophytic fungi were isolated from the fruits and leaves of P. Retrofractum and investigated for their antibacterial and antioxidant activities.Methods: All the isolated fungi were tested for their antibacterial activity using disc diffusion method with several series of concentrations and antioxidant capacity using the DPPH method. Result: The highest activity both antibacterial and antioxidant was demonstrated by DPR-1 extract against Staphylococcus aureus and Pseudomonas aeruginosa. This extract contained alkaloids, steroids, and flavonoid compounds.Conclusion: This study reported that endophytic fungi from P. retrofractum indicate as a potential source of bioactive and chemically novel compounds.Keywords: Piper retrofractum, endophytic fungi, antibacterial activity, antioxidant activity